2003
DOI: 10.1099/vir.0.19266-0
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a new species of kobuvirus associated with cattle

Abstract: A cytopathic agent was isolated using Vero cells from the culture medium of HeLa cells that had been used for more than 30 years in our laboratory. This agent, termed U-1 strain, was serially passed in Vero cells with distinct CPE. Particles of U-1 strain negatively stained with phosphotungstic acid exhibited a distinct surface that resembled Aichi virus. The RNA genome of U-1 strain comprises 8374 nt, with a genome organization analogous to that of picornaviruses. Possible cleavage sites of the large ORF, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
159
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 158 publications
(161 citation statements)
references
References 29 publications
0
159
0
2
Order By: Relevance
“…Of serum samples from 72 healthy cattle, 43 (59.7%) were positive for neutralizing antibody against bovine kobuvirus U-1 standard strain at a titer of >16. In addition, 12 (16.7%) of 72 stool samples collected from the cattle were positive for the bovine kobuvirus genome by reverse transcription-PCR (RT-PCR) (1). This fi nding suggested that bovine kobuvirus is common and that the virus particles could be detected in the stool samples of infected cattle.…”
Section: Bovine Kobuviruses From Cattle With Diarrheamentioning
confidence: 72%
See 4 more Smart Citations
“…Of serum samples from 72 healthy cattle, 43 (59.7%) were positive for neutralizing antibody against bovine kobuvirus U-1 standard strain at a titer of >16. In addition, 12 (16.7%) of 72 stool samples collected from the cattle were positive for the bovine kobuvirus genome by reverse transcription-PCR (RT-PCR) (1). This fi nding suggested that bovine kobuvirus is common and that the virus particles could be detected in the stool samples of infected cattle.…”
Section: Bovine Kobuviruses From Cattle With Diarrheamentioning
confidence: 72%
“…To date, the genus Kobuvirus consists of 2 species, Aichi virus and bovine kobuvirus (2). The Aichi virus is associated with acute gastroenteritis in humans (3)(4)(5); bovine kobuvirus infection has been detected only in cattle (1). Only 1 report has described the discovery and epidemiologic features of bovine kobuvirus (1).…”
Section: Bovine Kobuviruses From Cattle With Diarrheamentioning
confidence: 99%
See 3 more Smart Citations